Modeling and Simulation of Traffic Flow - Kaur, Satinder (My University, 2017)
The present thesis contained the brief study of Car Following Model, Continuum modeling and Lattice Hydrodynamic Models. The basics of traffic flow theory are studied briefly. Traffic flow modeling is classified and some earlier important work in the field is discussed concisely. The 1st chapter of the thesis introduce the traffic flow modeling and various models describing the traffic flow phenomenon. In 2nd chapter we have discussed about Car Following Models and its types. These models describes drivers behaviour only in the presence of interaction with other vehicles. The 3rd chapter contained Continuum Models and its various types. Chapter 4 we studied about Lattice hydrodynamic model.
Keywords: Lattice, Circuar Road, Traffic Flow, Driver Anticipation Effect